Electrical, magnetic and -optical -study of Gd3+ and Sm3+ ion doped at Fe-site in bismuth ferrite. (1st November 2022) - Padhy, Minakshi; Choudhary, R.N.P.; Achary, P. Ganga Raju
Abstract: The synthesis of two complex perovskites BiGd0.5 Fe0.5 O3 (BGFO) and BiSm0.5 Fe0.5 O3 (BSFO) was carried out by the doping of Gd 3+ and Sm 3+ ions at the B-site of bismuth ferrite by applying solid state/mixed oxide reaction method. The Rietveld analysis and X-ray diffraction pattern show that both BGFO and BSFO perovskites stabilize in the cubic-Fm3m phase. The FE-SEM study suggests an average grain size of 236.88 nm (BGFO) nm and 285.56 nm (BSFO). FTIR study shows the existence of Bi–O stretching vibration (BiO6 ) and Fe–O–Fe bending-vibration for BGFO and BSFO. The dielectric and impedance behaviors of these materials were studied in a wide range of temperatures (25 °C–500 °C) and frequencies (1 kHz–1000 kHz). The P-E hysteresis loop study shows a small remnant polarization with an energy storage density of 0.6163 J/cm 3 (BGFO) and 0.6053 J/cm 3 (BSFO). The energy storage efficiency ( η % ) of 66.49% and 76.85% is estimated for BGFO and BSFO respectively. Highlights: Gd 3+ and Sm 3+ ion doped at Fe-site in Bismuth Ferrite. P-E hysteresis loop study of BiGd0.5 Fe0.5 O3 . Electrical characteristics of BiGd0.5 Fe0.5 O3 . Dielectric characteristics of BiGd0.5 Fe0.5 O3 . Magnetic characteristics of BiGd0.5 Fe0.5 O3 .